2020
DOI: 10.1136/jech-2020-213885
|View full text |Cite
|
Sign up to set email alerts
|

Why does Russia have such high cardiovascular mortality rates? Comparisons of blood-based biomarkers with Norway implicate non-ischaemic cardiac damage

Abstract: BackgroundRussia has one of the highest rates of mortality from cardiovascular disease (CVD). At age 35–69 years, they are eight times higher than in neighbouring Norway. Comparing profiles of blood-based CVD biomarkers between these two populations can help identify reasons for this substantial difference in risk.MethodsWe compared age-standardised mean levels of CVD biomarkers for men and women aged 40–69 years measured in two cross-sectional population-based studies: Know Your Heart (KYH) (Russia, 2015–2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Efforts were made to accurately collect those data in comparable ways. A calibration study of biomarkers showed very small cross-laboratory differences in total cholesterol measurements between the two populations 40 , which made no substantial difference to our results. Furthermore, we need to acknowledge that our risk factor profiles come from three cities (two in Russia and one in Norway) and are not based on nationally representative samples.…”
Section: Discussioncontrasting
confidence: 63%
“…Efforts were made to accurately collect those data in comparable ways. A calibration study of biomarkers showed very small cross-laboratory differences in total cholesterol measurements between the two populations 40 , which made no substantial difference to our results. Furthermore, we need to acknowledge that our risk factor profiles come from three cities (two in Russia and one in Norway) and are not based on nationally representative samples.…”
Section: Discussioncontrasting
confidence: 63%
“…A calibration study between the two laboratories was conducted and HbA1c levels were adjusted appropriately to make them directly comparable. 18 We were not able to distinguish between type 1 and type 2 diabetes in this study as consistent and comparable data on age at onset and other distinctive characteristics of these two conditions were not available. Epidemiology/Health services research Exposure variables Adiposity was assessed using body mass index (BMI) and waist circumference (WC).…”
Section: Discussionmentioning
confidence: 66%
“…A calibration study between the two laboratories was conducted and HbA1c levels were adjusted appropriately to make them directly comparable. 18 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The question ‘Why does Russia have such high cardiovascular (CV) mortality rates?’ 1 can be answered by a pathologist who practised during the Soviet time. 2 Since then, the quality of postmortem examinations has decreased especially during the 1990s: autopsies were sometimes made perfunctorily.…”
mentioning
confidence: 99%